The Effect of Accessibility and Facilities on Return Interest with Tourist Satisfaction as Intervening Variable (Tourism of Boki Maruru Cave, Central Halmahera Regency) - Ibnu Sina Hi. Yusuf; Ririn Demayanti; Rheza Pratama (Budapest International Research and Critics University, 2022)
The objectives of this study are: 1. To examine the effect of Accessibility and Facilities on Tourist Satisfaction in Goa Boki Maruru; 2. To examine the effect of Accessibility and Facilities on Interest in Revisiting Goa Boki Maruru; 3. To examine the effect of Tourist Satisfaction on Interest in Revisiting Goa Boki Maruru; 4. To examine the role of Tourist Satisfaction in mediating the effect of Accessibility and Facilities on Interest in Revisiting Goa Boki Maruru. The number of samples in this study were 90 tourists, the sampling method was non-probability sampling and the sampling technique was porpusive sampling. The analytical test tool used is Partial Least Square (PLS) analysis. The results showed that: 1. Accessibility and Facilities have a significant effect on Tourist Satisfaction in Boki Maruru Cave; 2. Accessibility and facilities have no significant effect on interest in revisiting at Boki Maruru Cave; 3. Tourist Satisfaction has a significant effect on revisit interest in Boki Maruru Cave; 4. Tourist Satisfaction is able to mediate the influence of Accessibility and Facilities on Interest in Revisiting Goa Boki Maruru.